ANALISIS KUALITAS VEGETASI SEPANJANG PANTAI BANDA ACEH PASCATSUNAMI (THE VEGETATION QUALITY ANALISYS IN BANDA ACEH BEACH AFTER TSUNAMI) - Djufri, Djufri (Universitas Muhammadiyah Aceh, 2008)
The objectivees of this research were; to acquered of vegetation in Banda Aceh beach after tsunami, and else the research to find expression about of camposition, association, species diversity index (H’), similarity index (IS), and species distribution pattern. The stap of research were; observation and segmentation of study area. The size of study area is 420 ha, and sampel area is 10% of population. The station of sampling is (a). Ujung Batee Beach (UBB), (b). Lhoknga Beach (LB), and Ule Lee Beach (ULB). For each of sampling location a given ten of sampling quadrat with five replicatiion until of total sample is 50 quadrat. The observated variable is total species, absolute diversity, absolute frequency, and absolute dominance. The calculated of infortance value used formula is DR + FR + DMR., and calculated of species diversity index with Shannon-Wiener formula. The category of species diversity index is; if H’<1 very low category, H’>1-2 low category, H’>2-3 median category, and H’>3-4 high category. The result of this research; (a). The vegetation physiognomy in Ule Lee Beach was fundamental changed after tsunami, (b). The vegetation physiognomy in Ujung Batee Beach no significans changed after tsunami, (c). The planting of mangrove species in Ujung Batee Beach not yet optimal results, (d). Dominance of tree in Ujung Batee Beach and Loknga Beach is Casuarina equisetifolia, and Cocos nucifera, and dominance of underbrush is Calatropis gigantea, (5). For the moment effort necessary of serious reclamation in Banda Aceh Beach after tsunami specific. Key words: kualitas vegetasi, spesies